2021
DOI: 10.1371/journal.pone.0255854
|View full text |Cite
|
Sign up to set email alerts
|

Serum chemerin levels: A potential biomarker of joint inflammation in women with rheumatoid arthritis

Abstract: Background Chemerin has a potential role in perpetuating inflammation in autoimmune diseases. Nevertheless, to date, there is no conclusive information on whether high chemerin levels increase the severity of rheumatoid arthritis (RA). Therefore, this study evaluated whether serum chemerin is a biomarker of disease activity in RA patients. Methods Study design: cross-sectional. The assessment included clinical and laboratory characteristics, body mass index (BMI) and fat mass. The severity of the disease act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…There are no data on the effect of RARRES1 on the development of joint disease, but it has been shown to have pro-inflammatory and fibrosis-promoting effects through activation of the NF-κB signaling pathway [ 89 ]. RARRES2 (also known as chemerin) was overexpressed in the serum of OA [ 90 ] and RA [ 91 ] patients, but it was not correlated with disease stage. RARRES2 belongs to the adipokine family, and this protein may be a link between OA and obesity (its upregulation is confirmed in both disorders) [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are no data on the effect of RARRES1 on the development of joint disease, but it has been shown to have pro-inflammatory and fibrosis-promoting effects through activation of the NF-κB signaling pathway [ 89 ]. RARRES2 (also known as chemerin) was overexpressed in the serum of OA [ 90 ] and RA [ 91 ] patients, but it was not correlated with disease stage. RARRES2 belongs to the adipokine family, and this protein may be a link between OA and obesity (its upregulation is confirmed in both disorders) [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was performed by researchers of the Group for the Assessment of Prognosis Biomarkers in Autoimmune Disorders. The characteristics and members of this group had been published elsewhere [ 13 ]. This is a multidisciplinary group of researches estblished for the assessment of diagnostic tests, biomarkers, and prognosis and the treatment of chronic diseases.…”
Section: Methodsmentioning
confidence: 99%
“…This group was constituted by a multidisciplinary group of researchers (leadership: Laura Gonzalez-Lopez). Details of this group have been published elsewhere [ 13 ].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Gonzalez-Ponce et al [ 164 ] amplificated the results of the anterior study by implicating chemerin levels as a biomarker of joint inflammation in RA women. In an observational cross-sectional study, these authors identified in 210 patients (56.59 ± 11.25 years old) that chemerin serum levels were highly and positively associated with RA inflammation and moderate and severe RA diseases.…”
Section: General Aspects Of Ra and The Role Of Myokines Osteokines Ad...mentioning
confidence: 99%